Meningkatkan Kesehatan Masyarakat Desa Dirung Koram Kecamatan Kapuas Hulu Kabupaten Kapuas - Andi Tenri Abeng; Fikri Rahmadi; Septi Ayu Pratama; Sisi Eka Sari; Eva Wulandari; Muhammad Rasyid Ridho Ramlan; Siska; Pebi Wira Buana Paliapadang; Grace Rosally Monica; Muhamad Iqbal Ridhani; Evlin Lia Syaula B S; Elfrido Antasias; Krisna Murti (Jurnal Pengabdian Kampus, 2022)
Dirung Koram Village is part of Kapuas Regency, located in Kapuas Hulu District, Central Kalimantan. Dirung Koram was previously a hamlet part of the Tangirang village area. However, due to development and population growth, Dirung Koram was formed. Judging from the geographical conditions, Dirung Koram village is a village that can be said to have been left behind in several aspects, such as in terms of information technology so that important news from outside can not be obtained so quickly by the community, both from newspapers, television, and the internet. As a result, people have very little information, especially about the Covid-19 disease. Moreover, the village's location is quite far from other villages, and also from the socio-economic situation this village is still classified as very low which has an impact on the health of children. So, efforts were made to prevent the spread of Covid-19 by socializing the application of health protocols, stunting socialization, the Karhutla program (Forest and Land Fires), and installing banners to adopt new habits in Dirung Koram village. Through this method, it is hoped that the public can understand and be critical of the problems that are currently happening.